Penerapan Digital Marketing dalam Mendukung Kegiatan Pemasaran Pelaku UKM di Kabupaten Klungkung - Urmila Dewi, Made Heny; Trunajaya, I Gde; Kesumajaya, I Wayan Wita; Adigorim, I Made (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
Small and Medium Enterprises (Usaha Kecil dan Menengah / UKM) are one of the driving forces of the economy in Indonesia. One area that has a number of potential UKM but has not utilized digital marketing methods is Klungkung Regency, Bali Province. UKM in the area are currently still selling their products to the art market in Denpasar City and Semarapura whose results are uncertain. This is of course very unfortunate, very narrow marketing coverage results in turnover generated from the weaving is not optimal, even though the quality and uniqueness of the handicrafts produced should bring more sales turnover if able to penetrate a wider market share, without limitation space and time. The method of implementing the activity is divided into two stages. First, is to socialize the role of the internet for economic improvement in UKM. The second stage in this service will be exemplified how to create a simple website marketing (e-commerce) that can be applied directly to all participants who attended the socialization activity. After the training was carried out, continued with mentoring. This assistance activity is carried out in connection with the constraints faced by small and medium entrepreneurs in utilizing the internet. After the dissemination activities were carried out, it was found that some UKM claimed to be very interested in starting to use digital marketing models to support their marketing activities.